2020
DOI: 10.2147/cmar.s260866
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA GAS5 Targeting microRNA-21 to Suppress the Invasion and Epithelial–Mesenchymal Transition of Uveal Melanoma</p>

Abstract: Objective: Human uveal melanoma (UM) is a common ocular malignant tumor with a high risk of metastasis. Emerging evidence indicates that long non-coding RNAs (lncRNAs) are correlated with the development of UM. Here, we aimed to determine the biological significance of lncRNA growth arrest-specific transcript 5 (GAS5) in UM. Methods: The expression levels of GAS5 and microRNA-21 (miR-21) in UM tissues and cells were detected by qRT-PCR analysis. CCK-8 assay was performed to investigate the viability of UM cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…As a competing endogenous RNA for miR-96-5p, lncRNA GAS5 promotes renal tubular epithelial brosis (34). Likewise, LncRNA GAS5 directly bind to miR-21 to suppress EMT in human uveal melanoma (35). By coincidence, our previous research con rmed that lncRNA GAS5 can competitively combine with miR-21 to regulate PTEN and in uences EMT in HPMCs(36).…”
Section: Discussionmentioning
confidence: 93%
“…As a competing endogenous RNA for miR-96-5p, lncRNA GAS5 promotes renal tubular epithelial brosis (34). Likewise, LncRNA GAS5 directly bind to miR-21 to suppress EMT in human uveal melanoma (35). By coincidence, our previous research con rmed that lncRNA GAS5 can competitively combine with miR-21 to regulate PTEN and in uences EMT in HPMCs(36).…”
Section: Discussionmentioning
confidence: 93%
“…Genetic disruption via miR-NAs on the oncogenes or tumour suppressor genes may impact on malignant phenotypes of UM. Literature has shown that the pharmacological effects of miRNAs on UM are likely to be mediated through influencing cell proliferation and invasion [172,173]. Thus, miRNAs may be applicable in the diagnosis and prognosis of UM as well as with potential values in treating UM.…”
Section: Genetic Disruption Via Micrornas (Mirnas) In Ummentioning
confidence: 99%
“…In the last few decades, researchers have focused their attention on the role of lncRNAs in carcinogenesis [ 106 ]. Moreover, lncRNAs were found to be involved in the regulation of a plethora of cancer-related processes in UM [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Given the important contribution of lncRNAs to cancer progression, their potential application as circulating biomarkers has been investigated.…”
Section: Serum/plasma Circulating Long Rnas In Ummentioning
confidence: 99%